Understanding and managing in-stent restenosis: a review of clinical data, from pathogenesis to treatment - Buccheri, Dario; Piraino, Davide; Andolina, Giuseppe; Cortese, Bernardo (Journal of Thoracic Disease, 2016)
The lumen diameter reduction after percutaneous coronary intervention (PCI) is well known as “restenosis”. This phenomenon is due to vessel remodeling/recoil in case of no-stent strategy or, in case of stent employ, “neointimal proliferation” that consists in an excessive tissue proliferation in the luminal surface of the stent otherwise by a further new-occurring atherosclerotic process called “neoatherosclerosis”. The exact incidence of in-stent restenosis (ISR) is not easy to determine caused by different clinical, angiographic and operative factors. In the pre-stent era the occurrence of restenosis ranged between 32–55% of all angioplasties, and drop to successively 17–41% in the bare metal stents (BMS) era. The advent of drug-eluting stent (DES), especially 2nd generation, and drug-coated balloon (DCB) further reduce restenosis rate until